ANALYSIS CODE-SWITCHING IN ZHAFIRA AQYLA’S VLOG - Gina Oktaviani; Ningtyas Orilina Argawati; Evi Kareviati (IKIP Siliwangi, 2024)
Indonesia is happening in switching language and language style communication. There are many different types of media that we can use to see how code switching works, and one of them is Vlog. The purposes of this research, researchers to analyze the types of code-switching Zhafira Aqyla’s vlog and to identify the most dominant types of code-switching. This research used by using descriptive qulitative method. Based theory of (Wiley, 2019), the first step to start this research is to collect information through watching the videos. The second is researchers analyzed of available data. Then, the third compiles the results by categories the tyes of code-switching based on Poplack theory.